2013
DOI: 10.1590/s0100-204x2013000400012
|View full text |Cite
|
Sign up to set email alerts
|

Índices de vegetação simulados de diferentes sensores na estimativa das variáveis biofísicas do feijoeiro

Abstract: Resumo -O objetivo deste trabalho foi avaliar os índices de vegetação e bandas do vermelho e do infravermelho próximo, gerados a partir dos sensores HRVIR, ETM+ e Modis, nas estimativas de índice de área foliar e produtividade da cultura do feijoeiro. O experimento foi realizado em blocos ao acaso, com parcelas subdivididas, com quatro lâminas de irrigação (179,5, 256,5, 357,5 e 406,2 mm), três doses de N (0,0, 80,0 e 160,0 kg ha -1 ) e quatro repetições. As medidas de reflectância foram obtidas com o Spetron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…O NDVI se mostra como bom indicador do vigor vegetativo das plantas (MONTEIRO et al, 2013). Deste modo se espera que a observação de áreas com maiores valores de índices de vegetação em uma mesma população de plantas considerando condições normais, implicariam em maior vigor vegetativo e consequentemente em maiores produtividades.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O NDVI se mostra como bom indicador do vigor vegetativo das plantas (MONTEIRO et al, 2013). Deste modo se espera que a observação de áreas com maiores valores de índices de vegetação em uma mesma população de plantas considerando condições normais, implicariam em maior vigor vegetativo e consequentemente em maiores produtividades.…”
Section: Resultsunclassified
“…A grande vantagem do uso do sensoriamento remoto orbital para avaliação de áreas agrícolas consiste na agilidade, abrangência e baixo custo da tecnologia, uma vez que nos dias atuais vários produtos de média resolução são disponibilizados de maneira gratuita. As imagens derivadas destes satélites têm sido correlacionadas com vários fatores de interesse agrícola, dentre os quais a estimativa da produtividade em diferentes culturas tem grande destaque (LI et al, 2010;ESQUERDO;ZULLO JÚNIOR e ANTUNES, 2011;GROFF et al, 2013;MONTEIRO et al, 2013).…”
Section: Introductionunclassified
“…Remote sensing is now considered a powerful tool and unique data source for characterizing vegetation structure and development globally, and has played an increasing role in NPP estimates of ecosystems (Bao et al, 2016). The relationship between remote sensing and biophysical variables can be done by simple sensor bands and also by applying vegetation indices (Monteiro et al, 2013). Vegetation indices are often used to estimate vegetation parameters, and their physical basis is attributed to the high absorption of solar radiation by chlorophyll and their scattering by leaves in the red and near infrared spectral regions, respectively (Gates et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…This index also has a high correlation with vegetation cover percentage (Purevdorj et al, 1998) and green leaf biomass (Gitelson, Gritz, Merzlyak, 2003). In addition, it can be used to estimate biophysical parameters, such as leaf area index (LAI) and the fraction of photosynthetically active radiation that is absorbed (APAR) (Myneni, Williams, 1994), or even to compose models for crop yield estimations (Monteiro et al, 2013;Raun et al, 2001;Dorigo et al, 2007, Martorano, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that they are important tools in monitoring crop development (Risso et al, 2012) and correlate with grain yields (Bredemeier, Variani, Almeida, & Rosa, 2013;Monteiro, Angulo Filho, Xavier, & Monteiro, 2013). A time series of NDVI values of agricultural crops throughout their vegetative cycle can provide useful information on growth and crop state (Li et al, 2014).…”
mentioning
confidence: 99%